Digitalization of Transportation 5.0 Through Robotic Fishery Frozen Supply for Enhancing Aquatic Food Distribution in Demak City - Muhammad Ikhsan Setiawan; Agus Sukoco; Malikus Sumadyo; Elisa Sulistyorini; Adenanthera Lesmana Dewa; Che Zalina Zulkifli; Nafasov Mirzomurod Mukhamadovich; Fazilat Kodirova (Malikussaleh University, Aceh, Indonesia, 2026)
The transformation of fishery product distribution systems has become increasingly important in ensuring food security, supply chain efficiency, and economic resilience in coastal regions. As demand for high-quality aquatic food products continues to grow, conventional logistics systems often face challenges related to post-harvest losses, inefficient transportation, limited traceability, and inadequate cold chain management. This research investigates the application of Digitalization 5.0 in transportation logistics through an integrated Robotic Fishery Frozen Supply system to enhance the distribution of aquatic food products in Demak City, Indonesia. The proposed framework combines autonomous robotic loading and unloading technologies, Internet of Things (IoT)-based cold chain monitoring, real-time logistics management, and blockchain-enabled traceability to create a smart and sustainable fishery distribution ecosystem. The study employs a mixed-methods approach, integrating qualitative assessments through stakeholder interviews and focus group discussions with quantitative evaluations of logistics performance, distribution efficiency, cold chain stability, and operational cost-effectiveness. The findings demonstrate that the implementation of the Robotic Fishery Frozen Supply model significantly improves distribution performance by reducing post-harvest losses by 27%, shortening delivery times by 35%, and enhancing transparency and accountability throughout the supply chain. In addition, the system contributes to maintaining product quality, minimizing food waste, and improving market access for local fishery producers. The research further reveals that the Digitalization 5.0 framework supports sustainable development by integrating human-centered innovation, automation, and environmental responsibility. The proposed model aligns with the Sustainable Development Goals (SDGs), particularly Goal 2 (Zero Hunger), Goal 9 (Industry, Innovation and Infrastructure), and Goal 12 (Responsible Consumption and Production). The novelty of this study lies in the convergence of autonomous robotic technologies, Digitalization 5.0 principles, and sustainable fishery logistics, offering a scalable and replicable model for coastal regions in developing countries seeking to modernize aquatic food distribution systems while strengthening economic sustainability and food security